The Impact Analysis of Population and Intensity of The Brown Badge (Leptocorisa Oratorius F.) Attacks on Rice Production in Waisika Village, Alor Timur Laut District - Molebila, Didiana Yanuarita; Maitia, Jitro A.; Maure, Gerson Hans (JURNAL AGRIBISAINS, 2026)
The brown planthopper is a major pest of rice plants, and its presence causes damage and yield loss in Waisika Village. This impacts total rice production during a growing season. As a baseline for decision-making regarding control measures, this study aims to analyze the population density and attack intensity of the rice bug (Leptocorisa oratorius F.) as well as its impact on rice production in Waisika Village, Alor Regency, an area currently experiencing a food deficit. The rice bug attacks during the generative (milky ripening) stage and has the potential to cause empty grains and yield losses of up to 50%. The research was conducted using a purposive sampling technique on nine observation plots (1 m × 1 m) from March to June 2025. The observed variables included pest population density (individuals/100 m²), pest attack intensity (IS) (%), and total rice yield (g/clump). The results showed that the population density of the rice bug fluctuated between 8.11 and 13.78 individuals per 100 m². The attack intensity (IS) of the rice bug increased from the first to the third week, reaching the highest average of 42.17%, which is categorized as a moderate attack level. However, the results of the simple linear regression analysis indicated that the population density and attack intensity of the rice bug had an insignificant effect (Sig. = 0.653) on rice production. This insignificant impact is likely: 1. The damage caused was not absolute, allowing the rice plants to continue producing grain. 2. The farmers used pest-resistant superior rice varieties (Inpari 34 and Inpari 35). 3. The cultivation area consisted of a wide expanse of rice fields, allowing the pest to move from one area to another, thereby reducing significant damage in any specific location. The moderate attack level (42.17%) requires further brown planthopper control measures to suppress pest outbreaks.